Linguagem, língua e desenvolvimento humano: por um nó teórico-epistemológico entre interacionismo sociodiscursivo e psicanálise - Menezes, Renata de Lourdes Costa de (2018)
Based on transdisciplinary principles, the general objective of this study is to reconfigure the notion of human development and its implications in the emergence of the subject from language and by language since the interlocution between the Sociodiscursive Interactionism (SDI) and Psychoanalysis, through their representatives: Jean Paul Bronckart and Donald Woods Winnicott, respectively. For this purpose, we carried out a bibliographical and exploratory research whose discussion emerged from one of Bronckart’s critical text (BRONCKART, 2006b) on the vigotskian human ontogenetic development scheme. In this sense, we first characterize Bronckart's points of tension (2006a; 2006b; 2006c) between his thought and Vigotsky's work and how those disagreements lead the author himself to propose a new approach to the question of human development in a perspective that he called "rebuilding" (BRONCKART, 2006b). We present Winnicott's theory of primitive emotional development (1975, 1988, 2000, 2011, 2012), and we discuss how winnicottian monistic thinking interrelates and gives meaning to the criticism of Bronckart’s concepts, helping to print a new vision on the issues of development, conditioned, above all, by environmental and interrelational exchanges. Finally, we build a new scheme of human development based on the dialogue between Bronckart and Winnicott, emphasizing, above all, the importance of the language in this process. By accomplishing that proposal, we corroborate the thesis that the Winnicottian psychoanalytic principles, in some way, are compatible with fundamental positions and the theoretical-epistemological discussions developed by the precursor of SDI.